2021
DOI: 10.1021/acsomega.1c03779
|View full text |Cite
|
Sign up to set email alerts
|

Examining a Transition from Supramolecular Halogen Bonding to Covalent Bonds: Topological Analysis of Electron Densities and Energies in the Complexes of Bromosubstituted Electrophiles

Abstract: The transition from weak (noncovalent) interactions to fully developed covalent bonds is examined using the quantum theory of atoms in molecules in a series of halogen-bonded (XB) complexes of bromosubstituted electrophiles, RBr, with 1,4-diazabicyclo[2.2.2]octane (DABCO) and Cl – and Br – anions. The gradual decrease in the XB lengths in these associations, d Br···Y (where Y = Cl – , Br – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 54 publications
5
15
0
Order By: Relevance
“…The BCPs located on the bond paths along the shortest S–S separations are characterized by electron densities of about 0.009 au, energy densities of about 0.0012 au and Laplacians of electron density of about 0.027 au. All of these values are comparable to the characteristics found for moderately strong halogen and hydrogen bonds. Furthermore, a noncovalent indices (NCI) analysis showed mostly green surfaces representing nonbonding interactions between TMTTF moieties with blue spots indicating bonding interactions around the areas adjacent to the (3, −1) BCPs.…”
Section: Resultssupporting
confidence: 65%
“…The BCPs located on the bond paths along the shortest S–S separations are characterized by electron densities of about 0.009 au, energy densities of about 0.0012 au and Laplacians of electron density of about 0.027 au. All of these values are comparable to the characteristics found for moderately strong halogen and hydrogen bonds. Furthermore, a noncovalent indices (NCI) analysis showed mostly green surfaces representing nonbonding interactions between TMTTF moieties with blue spots indicating bonding interactions around the areas adjacent to the (3, −1) BCPs.…”
Section: Resultssupporting
confidence: 65%
“…Following the earlier QTAIM studies of the HB and HaB associations, [27][28][29][30][31][32] we focused our analysis on electron densities, r(r), the Laplacians, r 2 r(r), kinetic and potential energy densities G(r) and V(r), and energy density H(r) = G(r) + V(r). These characteristics evaluated in the solid-state and optimized structures at the BCPs along the SeÁ Á ÁBr and TeÁ Á ÁI bond paths are listed in Tables S3-S6 in the ESI.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28] Previous applications of QTAIM to the series of hydrogen-bonded (HyB) and HaB complexes demonstrated continuous variations of the characteristics of these bond critical points (BCPs) with a decrease in the interatomic distances from the van der Waals separations to the covalent bonds. [28][29][30][31][32] Based on the topology of electron densities and energies at BCPs, the interactions in these systems were classified as non-covalent (closed-shell), covalent (shared-shell) and intermediate (partially-covalent) bonding. 29,31 Moreover, synchronous changes of the bonding characteristics with the normalized interatomic separations, R XY = d XY /(R X + R Y ) (where d XY is an interatomic X-Y distance, and R X and R Y are van der Waals radii of X and Y) in the HaB systems suggested that R XY could be used for the classification of the interactions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations